Infection by Bacteriophage P1 and Development of Host-controlled Restriction and Modification and of Lysogenic Immunity - Werner, Elizabeth R. (1969)
Shigella dysenteriae cells were infected with phage P1 or P1cl. The outcome of superinfection of these cells with phage T1.Sh or T1.Sh(P1) or P1cl was studied as a function of time after the initial infection. Cells undergoing either a lytic response or a lysogenic response to the primary infection develop the ability to specifically restrict T1.Sh between 30 and 45 min. Between 15 and 30 min, the cells seem to develop the ability to produce T1.Sh(P1) after infection by T1.Sh. However, reasons are given for believing that this apparent time difference is consistent with a simultaneous development of the two capacities (restriction and modification) within the cell. This development occurs between 30 and 45 min. Cells infected with P1cl and superinfected 45 or more min later with T1.Sh(P1) can yield both P1cl and T1. Cells infected with P1 become resistant to infection by P1cl within 5 to 10 min. It is argued that this early immunity is not necessarily different in mechanism from true lysogenic immunity.